Cinematic Design and Force Analysis of a SCARA Robot with Pneumatic Actuators (LACCEI, 2024)
The use of pneumatics applied to industry is greatly favored by its great availability and for being a non-polluting fluid, thus having a potential to replace other systems in the industry. In the field of industrial robotics, a robotic arm with pneumatic servomotors is rarely designed, as there are few studies about it. This technology being a closed loop repetitive control system with feedback makes feasible its implementation for processes in the industry. Since there are few pneumatic industrial robots, this study seeks to design a prototype using 3D printing with a pneumatic system. Also, the necessary information on the mechanical adjustments in the pneumatic actuators for a required application as well as the interpretation of transmission simulations. This study provides a manufacturing model of a fully pneumatic and functional robotic prototype, showing the advantage of using belts for transmission mechanisms and 3D printing manufacturing. This also opens the field for future research on pneumatic control applied to industrial robotics.